2019
DOI: 10.1186/s12875-019-0910-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding accreditation standards in general practice – a qualitative study

Abstract: BackgroundAccreditation is a widely adopted tool for quality control and quality improvement in health care, which has increasingly been employed for general practice. However, there is lack of knowledge of how accreditation is received and experienced by health professionals in general practice. This study explores how general practitioners (GPs) and their staff experienced the comprehensibility of accreditation standards and how they worked to increase their understanding of the standards. The study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 19 publications
0
33
0
1
Order By: Relevance
“…- Reading, understanding and discussing the standards and their implications for the clinic and describing practice procedures in formal documents. This work could include participation in regional information meetings and workshops (see also [16]);…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…- Reading, understanding and discussing the standards and their implications for the clinic and describing practice procedures in formal documents. This work could include participation in regional information meetings and workshops (see also [16]);…”
Section: Resultsmentioning
confidence: 99%
“…Having received notification of the date of their survey visit, the clinics had 1 year to prepare for the visit. During this period of accreditation various agencies offered some kind of support to clinics preparing for the survey visit [16]. Approximately 1 year after the notification date, the clinics received a survey visit by two surveyors who questioned the GPs and the staff to determine whether the clinic adhered to the accreditation standards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey and interview data suggest that the standards used for inspections must be valid, focused on clinical practice and benefits for the patients, and should be translated into something perceived as relevant and useful for the services in their improvement work. 36 44–50 To be perceived as relevant, the standards should be adapted to the local context. 51 52 Development and revision of standards require a collaborative approach and the expertise of a range of stakeholders including the patients.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32][33][34] Four other studies reported that the self-assessment tool was confusing and time consuming and was concerned with finding and producing documentation rather than reviewing practice. [35][36][37][38] Four case studies, three using interview data and one using time series analysis of performance indicators Open access found that most substantial changes were made during the self-assessment phase, 36 39-41 where as one study using interview data found that the organisation did not make improvements during the self-assessment phase because it was considered sufficient just to identify improvement needs. 42 Another case study found that changes made before the site visit were superficial and sought to achieve ritual compliance, focusing more on getting through the inspection process than on really improving the quality of care.…”
Section: Self-assessmentmentioning
confidence: 99%